Bad to the Bone: The Effects of Therapeutic Glucocorticoids on Osteoblasts and Osteocytes - Gado, Manuel; Baschant, Ulrike; Hofbauer, Lorenz C.; Henneicke, Holger (Frontiers in Endocrinology, 2022)
Despite the continued development of specialized immunosuppressive therapies in the form of monoclonal antibodies, glucocorticoids remain a mainstay in the treatment of rheumatological and auto-inflammatory disorders. Therapeutic glucocorticoids are unmatched in the breadth of their immunosuppressive properties and deliver their anti-inflammatory effects at unparalleled speed. However, long-term exposure to therapeutic doses of glucocorticoids decreases bone mass and increases the risk of fractures – particularly in the spine – thus limiting their clinical use. Due to the abundant expression of glucocorticoid receptors across all skeletal cell populations and their respective progenitors, therapeutic glucocorticoids affect skeletal quality through a plethora of cellular targets and molecular mechanisms. However, recent evidence from rodent studies, supported by clinical data, highlights the considerable role of cells of the osteoblast lineage in the pathogenesis of glucocorticoid-induced osteoporosis: it is now appreciated that cells of the osteoblast lineage are key targets of therapeutic glucocorticoids and have an outsized role in mediating their undesirable skeletal effects. As part of this article, we review the molecular mechanisms underpinning the detrimental effects of supraphysiological levels of glucocorticoids on cells of the osteoblast lineage including osteocytes and highlight the clinical implications of recent discoveries in the field.